A Mendelian randomization study to assess the genetic liability of type 1 diabetes mellitus for IgA nephropathy - Deng, Peizhi; Li, Zhixin; Yi, Bin; Leng, Yiping (Frontiers in Endocrinology, 2022)
Background: The prevalence of immunoglobulin A nephropathy (IgAN) seems to be higher in patients with type 1 diabetes mellitus (T1DM) than in the general population. But whether there exists a causal relationship between T1DM and IgAN remains unknown. Methods: This study conducted a standard two-sample Mendelian randomization (MR) analysis to assess the causal inference by four MR methods and the inverse variance weighted (IVW) approach was picked as the primary method. To further test the independent causal effect of T1DM on IgAN, multivariable MR (MVMR) analysis was undertaken. Sensitivity analyses incorporating multiple complementary MR methods were applied to evaluate how strong the association was and identify potential pleiotropy. Results: MR analyses utilized 81 single nucleotide polymorphisms (SNPs) for T1DM. The evidence supports a significant causal relationship between T1DM and increased risk of IgAN (Odds ratio [OR]: 1.39, 95% confidence interval [CI]: 1.10 to 1.74 for IVW, p < 0.05). And such association still exists after adjusting for triglyceride (TG), fasting insulin (FI), fasting blood glucose (FBG), homeostasis model assessment of beta-cell function (HOMA-B) and insulin resistance (HOMA-IR), and glycated hemoglobin (HbA1c). MVMR analysis indicated the effect of T1DM on IgAN vanished upon accounting for low density lipoprotein cholesterol (LDL-c, OR: 0.97, 95% CI: 0.90 to 1.05, P > 0.05). Conclusions: This MR study provided evidence that T1DM may be a risk factor for the onset of IgAN, which might be driven by LDL-c. Lipid-lowering strategies targeting LDL-c should be enhanced in patients with T1DM to prevent IgAN.